2019
DOI: 10.1037/ort0000417
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the foundation: Culturally congruent mentoring for research scholars and faculty from underrepresented populations.

Abstract: here are scores of university faculty and scholars from diverse backgrounds who have long researched, preached about, and presented statistics and reports to illustrate the direct and indirect effects of generations of policies and practices that have resulted in disparities in health and mental health in our country (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The development of community-centered relationships with key community stakeholders provided researchers with an opportunity to strengthen their knowledge-base of Black MSM communities in connection to research. This type of cultural connection allows researchers to work in collaboration with communities who have experienced multiple forms of exclusion and marginalization when conducting culturally-grounded community research, as well as addressing the needs of Black MSM based on critical research questions [40,58].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The development of community-centered relationships with key community stakeholders provided researchers with an opportunity to strengthen their knowledge-base of Black MSM communities in connection to research. This type of cultural connection allows researchers to work in collaboration with communities who have experienced multiple forms of exclusion and marginalization when conducting culturally-grounded community research, as well as addressing the needs of Black MSM based on critical research questions [40,58].…”
Section: Discussionmentioning
confidence: 99%
“…Having researchers who are aware of the nuances of these socio-cultural frameworks within Black MSM communities became important in developing a protocol that was inclusive of such a diverse population [59][60][61]. Moreover, when conducting research on Black communities, Wyatt et al [40] indicated that the institutional context of exclusion for Black researchers needs to be considered when integrating culturally-congruent research approaches (e.g., historical, socio-cultural/-structural and personal barriers related to disenfranchisement from the research process). A core component of this work involves the inclusion of researchers that are representative of Black MSM communities and maintain values that are congruent with Black MSM communities [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations